2007
DOI: 10.1111/j.1365-2133.2007.08146.x
|View full text |Cite
|
Sign up to set email alerts
|

Hairdressing and the prevalence of scalp disease in African adults

Abstract: We found associations between specific scalp diseases, hairstyles, gender, and age. These associations need further study, better to elucidate determinants and to improve disease prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 17 publications
8
139
4
1
Order By: Relevance
“…In male partners of female participants, the prevalence of FKN was similar to the male population data (10.05% v. 10.5%), and in female partners of male participants it was higher, but again not significantly higher, than the female population data (1.4% v. 0.3%; p=0.12). Although the prevalence of haircut-associated bleeding was lower than in the previous study [1] (but not significantly lower, 24.6% v. 32%; p=0.17), it was noteworthy that bleeding was common in both studies. Additionally, more participants had a history of bleeding from a haircut than were diagnosed with FKN, suggesting that this haircut increases the risk of bleeding even in people with healthy scalps.…”
Section: Fig 1 a Patient With Keloidal Papules And Plaques On The Ncontrasting
confidence: 47%
See 3 more Smart Citations
“…In male partners of female participants, the prevalence of FKN was similar to the male population data (10.05% v. 10.5%), and in female partners of male participants it was higher, but again not significantly higher, than the female population data (1.4% v. 0.3%; p=0.12). Although the prevalence of haircut-associated bleeding was lower than in the previous study [1] (but not significantly lower, 24.6% v. 32%; p=0.17), it was noteworthy that bleeding was common in both studies. Additionally, more participants had a history of bleeding from a haircut than were diagnosed with FKN, suggesting that this haircut increases the risk of bleeding even in people with healthy scalps.…”
Section: Fig 1 a Patient With Keloidal Papules And Plaques On The Ncontrasting
confidence: 47%
“…[1,2] We obtained approval from the Ethics Committee of the Faculty of Health Sciences, University of Cape Town, permission from the Cape Town Central Health District, Western Cape, and informed consent from participants. Our aim was to compare the prevalences of haircut-associated bleeding and FKN with existing Langa population data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although TA is more prevalent among females of African ancestry, it has been described in a wide range of populations, including nurses, ballerinas, Sikh boys and men, to name a few [30][31][32][33][34]. Research has convincingly demonstrated that certain habitual practices of hairstyling are implicated in the pathogenesis of TA [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%